Komposisi Hasil Tangkapan dan Tingkat Keramahan Jala Cumi (Cast Net) di PPN Kejawanan Cirebon Jawa Barat - Dedi Supriadi; Sri Rahayu; Andi Perdana Gumilang (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2020)
Fishing Port of Nusantara Kejawanan Cirebon, located in the eastern part of West Java, is a type B port that is dominated by ships with squid fishing equipment (cast net) with a total of 123 vessels. The purpose of this study is to analyze the composition of catch and level friendliness of squid fishing gear (cast net) based on the composition of the main catch and by catch. Data collection was carried out descriptively through surveys. Data on fish catches were collected from 10 units of cast net fishing gear units in 2018. Data analysis includes the composition of the type of catch and its level of friendliness. Based on the results of the study showed that the squid fishing gear (cast net) with the composition of the catch is dominated by squid by 97% and the remaining 3% consists of lemuru, kite and anchovies. The size of the squid catch that was landed in the Fishing Port of Nusantara Kejawanan Cirebon has a size with a category of large squid 27-30 cm with a total amount of 79,324.64 kg and small size squid with a total size of 1-7 cm with a total number of 18,411.29 kg. The value of the level of environmental friendliness in squid fishing gear (cast net) is obtained with a total value of 30. Based on these values ​​the squid fishing gear (cast net) is categorized as a very environmentally friendly fishing gear.